STATE BENEFITS AND REQUIREMENTS OF STATE DOCUMENTATION OF LANDS - Joldasbaeva Umida Jalgasbayevna; Reimov Niyetbay Baynazarovich (American Journals Publishing, 2025)
The article sets out a number of new requirements for the legalization of rights to illegally occupied land plots and buildings and structures erected on them, and also provides new benefits to landowners and the termination of illegal occupation. A brief overview of scientific research on the provision of benefits in relation to illegally occupied land plots and buildings and structures constructed on them in the Republic of Karakalpakstan is presented.
Keywords: Republic of Uzbekistan, Karakalpakstan, autonomy, land plot, decisions, document, law, building, structure, responsibility.